Inside it was orange squash concentrate: trainees' experiences of reflective practice groups within clinical psychology training. Issue 1 (2nd January 2019) - Lyons, Amy; Mason, Barbara; Nutt, Katherine; Keville, Saskia
ABSTRACT: Despite many clinical psychology training programmes utilising reflective practice groups (RPGs) to develop reflective practice (RP) skills, there remains little research examining how trainees experience these groups. This study uses interpretative phenomenological analysis (IPA) to explore the experiences of eight qualified clinical psychologists who attended RPGs on one United Kingdom (UK) clinical psychology training programme. A purposive sample was recruited for single, semi-structured interviews. Five superordinate themes were identified: 'The process: there were so many layers'; 'The impact: an ongoing process'; 'Commitment: I hated it, but I still went'; 'The facilitator: a presence who was not always present'; and 'Getting through it: finding ways to cope'. The findings illustrate the varied and complex experiences of the participants. Whilst the experience was often difficult, the participants were committed to attending and sought out ways to navigate it. The results are conceptualised in terms of existing psychological theory and literature. A critique of the research and suggestions for future studies are offered, including exploring the views of group facilitators and comparing how groups are utilised within different training programmes. Recommendations are made on the development of future RPGs, which include consideration of the facilitation style and the groups' frequency and size.